Does ant richness and composition respond to phytophysiognomical complexity and seasonality in xeric environments? - Emerson Mota Silva; Anderson Matos Medina; Ivan Cardoso Nascimento; Priscila Paixão Lopes; Karine S. Carvalho; Gilberto M. M. Santos (Sociobiology)
This study aims to analyze how the vegetation structure (physiognomy) and seasonal changes between seasons (wet and dry) influence richness, diversity and composition of ant species of arboreal and shrubby Caatinga environments. The vegetation structure was significantly different among the three strata for all parameters (mean diameter of vegetation, level of herbaceous cover, degree of coverage and thickness of litter and percentage of canopy cover). We collected 127 ant species. The mean number of species was approximately two times higher in the rainy season than in the dry season. There was no difference in species richness between the arboreal and shrubby Caatinga physiognomies nor interaction between season and physiognomy. Despite the similarity in richness, species composition differed between physiognomies, however we found no difference in composition between seasons. The seasonal differentiation may be mainly related to the variation in the overall numbers of individuals circulating in the environment, since the enhancement of resource availability during rainy season allows the colony to grow or expand foraging activities, which increases local diversity. Water restriction explains the limited diversity in both environments, while the occurrence of species with greater resource specificity may determine differences in ant composition. Differences in composition of each of Caatinga's physiognomy enhance beta diversity, therefore, raising the overall diversity in the Caatinga Domain.